Endopeptidase Cleavage Generates a Functionally Distinct Isoform of C1q/Tumor Necrosis Factor-related Protein-12 (CTRP12) with an Altered Oligomeric State and Signaling Specificity - Wei, Zhikui (American Society for Biochemistry and Molecular Biology, 2012)
Adipose tissue-derived adipokines are an important class of secreted metabolic regulators that mediate tissue cross-talk to control systemic energy balance. We recently described C1q/TNF-related protein-12 (CTRP12), a novel insulin-sensitizing adipokine that regulates glucose metabolism in liver and adipose tissue. However, the biochemical properties of CTRP12 and its naturally occurring cleaved isoform have not been characterized. Here, we show that CTRP12 is a secreted hormone subjected to multiple functionally relevant posttranslational modifications at highly conserved residues. For example, Asn(39) is glycosylated, whereas Cys(85) mediates the assembly of higher order oligomeric structure. Endopeptidase cleavage at Lys(91) generates a cleaved globular gCTRP12 isoform, the expression of which is increased by insulin. PCSK3/furin was identified as the major proprotein convertase expressed by adipocytes that mediates the endogenous cleavage of CTRP12. Cleavage at Lys(91) is context-dependent: mutation of the charged Arg(93) to Ala on the P2′ position enhanced cleavage, and triple mutations (K90A/K91A/R93A) abolished cleavage. Importantly, the two isoforms of CTRP12 differ in oligomeric structures and are functionally distinct. The full-length protein forms trimers and larger complexes, and the cleaved isoform consisted of predominantly dimers. Whereas full-length fCTRP12 strongly activated Akt signaling in H4IIE hepatocytes and 3T3-L1 adipocytes, gCTRP12 preferentially activated MAP kinase (ERK1/2 and p38 MAPK) signaling. Further, only fCTRP12 improved insulin-stimulated glucose uptake in adipocytes. These results reveal a novel mechanism controlling signaling specificity and function of a hormone via cleavage-dependent alteration in oligomeric state.